Opening speech - Hallberg, Anders (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Mr President of LIBER, Mr Chancellor of Justice (JK Göran Lambertz finns med i publiken), and Distinguished Heads and Representatives of important European Libraries, First, a warm welcome to all of you in Uppsala and Sweden. It is, for reasons unknown to me, actually the first time in your Association’s 35 years proud history that you convene in this country.